Pengaruh Stres Peran Terhadap Turnover Intention Dengan Keterikatan Kerja Sebagai Variabel Mediasi di The 101 Bali Fontana Seminyak - Ni Putu Intan Sari; I Putu Esa Widahartana; Ida Ayu Kalpikawati (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2022)
Pressures and problems in the hospitality industry due to the COVID-19 pandemic have made many hotel employees stop working and employees who are still working have to work in multiple roles. Employees who work in multiple roles are now slowly quitting their jobs due to role stress. Role stress can have a negative impact on companies such as reducing a sense of work engagement and increasing turnover intention. Therefore, this study aims to analyze the effect of role stress on turnover intention with work engagement as a mediating variable at The 101 Bali Fontana Seminyak. Data were collected by distributing questionnaires to 46 hotel employees. The data from the questionnaire were then analyzed using the classical assumption test, path analysis test, coefficient of determination test, and Sobel test. The results of data analysis found that role stress had a positive impact on turnover intention and a negative effect on engagement. Work engagement was found to have a negative effect on turnover intention. Work engagement was found to partially mediate this relationship. This study suggests the hotel to provide clear briefings to employees, build a comfortable work environment, and take a persuasive approach to employees.